Comparison of behavioral treatment conditions in buprenorphine maintenance. (12th July 2013) - Ling, Walter; Hillhouse, Maureen; Ang, Alfonso; Jenkins, Jessica; Fahey, Jacqueline
Abstract: Background and aims: The Controlled Substances Act requires physicians in the United States to provide or refer to behavioral treatment when treating opioid‐dependent individuals with buprenorphine; however, no research has examined the combination of buprenorphine with different types of behavioral treatments. This randomized controlled trial compared the effectiveness of four behavioral treatment conditions provided with buprenorphine and medical management (MM) for the treatment of opioid dependence. Design: After a 2‐week buprenorphine induction/stabilization phase, participants were randomized to one of four behavioral treatment conditions provided for 16 weeks: cognitive behavioral therapy (CBT = 53); contingency management (CM = 49); both CBT and CM (CBT + CM = 49); and no additional behavioral treatment (NT = 51). Setting: Study activities occurred at an out‐patient clinical research center in Los Angeles, California, USA. Participants: Included were 202 male and female opioid‐dependent participants. Measurements: Primary outcome was opioid use, measured as a proportion of opioid‐negative urine results over the number of tests possible. Secondary outcomes include retention, withdrawal symptoms, craving, other drug use and adverse events. Findings: No group differences in opioid use were found for the behavioral treatment phase (χ 2  = 1.25, P  = 0.75), for a second medication‐only treatment phase, or at weeks 40 and 52 follow‐ups. Analyses revealed no differences across groups for any secondary outcome. Conclusion: There remains no clear evidence that cognitive behavioural therapy and contingency management reduce opiate use when added to buprenorphine and medical management in opiate users seeking treatment.